Bridging Financial Gaps: A Qualitative Literature Review on Government Loan Programs and Small Business Growth under Credit Constraints - Benardi Benardi; Novrizal (LPPM STIE Kasih Bangsa, 2026)
This qualitative literature review examines the role of government loan programs in addressing credit constraints that hinder small business growth. Synthesizing recent empirical studies from Japan, the United States, and the European Union, the review finds that well-targeted public lending initiatives facilitate capital investment, employment expansion, and long-term productivity among financially constrained firms. The evidence highlights that government credit often complements rather than substitutes private lending and serves as a structural mechanism to reduce financial frictions. Program effectiveness is found to depend heavily on institutional design, eligibility targeting, and administrative capacity. The findings underscore the strategic value of sustained public intervention in SME finance, not only during crises but also for long-term economic resilience and inclusive growth